Supplementary Food with Potato and Moringa Sticks as an Effort to Introduce Nutritional Variations for Toddlers - Dini Ariani; Hani Septiani; Irpan Ali Rahman (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The nutritional status of children greatly affects their physical growth and brain development. For this reason, it is necessary to provide variations in the provision of additional food from available ingredients at economical prices and good nutritional content. Additional food can be obtained from processing potatoes and Moringa. The aim of this community service activity is to provide knowledge about variations in food from potatoes and Moringa leaves that are processed into sticks The method used is by providing health education about moringa, malnutrition, stunting and demonstrating the making process of potalor stick. The target of this activity is all pregnant women and mothers of children under five who come to Posyandu Mawar. The result of this program reveals an increase in knowledge about moringa, malnutrition, stunting and processing stik potalor. Pregnant women and mothers of toddlers know and understand the incidence of stunting, and know how to make potalor stick.